Welfare Regimes in Latin America: Capturing Constellations of Markets, Families, and Policies - Martínez Franzoni, Juliana (2008)
This article presents both a theoretical framework and a methodology that attempt to capture the complex interactions among labor markets, families, and public policy that currently constitute Latin American welfare regimes. Drawing on cluster analysis based on available data for 18 countries, the study identifies three welfare regimes. Two are state welfare regimes: protectionist (e.g. Costa Rica) and productivist (e.g. Chile); one is nonstate familiarist (e.g. Ecuador and Nicaragua). In a region where people's well‐being is deeply embedded in family relationships, closer scholarly attention to how social structures interact with public policy bears not only academic interest but also policy implications, particularly for adapting particular welfare regimes to the local welfare mix.